Dentin and dental pulp regeneration by the patient’s endogenous cells - KIM, SAHNG G. (2013)
The goal of regenerative endodontics is to restore the functions of the dental pulp–dentin complex. Two approaches are being applied toward dental pulp–dentin regeneration: cell transplantation and cell homing. The majority of previous approaches are based on cell transplantation by delivering ex vivo cultivated cells toward dental pulp or dentin regeneration. Many hurdles limit the clinical translation of cell transplantation such as the difficulty of acquiring and isolating viable cells, uncertainty of what cells or what fractions of cells to use, excessive cost of cell manipulation and transportation, and the risk of immune rejection, pathogen transmission, and tumorigenesis in associated with ex vivo cell manipulation. In contrast, cell homing relies on induced chemotaxis of endogenous cells and therefore circumvents many of the difficulties that are associated with cell transplantation. An array of proteins, peptides, and chemical compounds that are yet to be identified may orchestrate endogenous cells to regenerate dental pulp–dentin complex. Both cell transplantation and cell homing are scientifically valid approaches; however, cell homing offers a number of advantages that are compatible with the development of clinical therapies for dental pulp–dentin regeneration.